Mental well-being and sleep quality among vocational college students in Sichuan, China during standardized COVID-19 management measures - Gao, Ru; Wang, Hailian; Liu, Shan; Wang, Xia; Xiong, Xiaomei; Song, Si-Yuan; Wang, Yi (Frontiers in Public Health, 2024)
Purpose This research investigated the impact of the COVID-19 pandemic on the mental well-being and sleep quality of students in higher vocational colleges in Sichuan, China, identifying key factors influencing their psychological health during this period. Methods Between January and February 2022, a comprehensive survey was conducted among students from several higher vocational colleges in Sichuan, utilizing a randomized selection approach to involve 3,300 participants. Data were collected through direct interviews executed by skilled interviewers. Results Out of 3,049 valid responses, a significant number reported experiencing symptoms of poor mental health, anxiety, depression, and insomnia, with prevalence rates of 21.2%, 9.7%, 14.1%, and 81.9%, respectively. Factors contributing positively to mental health and sleep included a higher family economic status, reduced stress from the pandemic, and decreased online activity. Conversely, lack of physical activity post-pandemic, disruptions to education and employment, and deteriorating relationships emerged as negative influencers. Interestingly, a lack of pre-pandemic mental health knowledge acted as a protective factor against insomnia. Conclusion The ongoing management of COVID-19 has notably influenced the psychological and sleep health of vocational college students, driven by economic, emotional, lifestyle, and educational factors. The findings underscore the necessity for targeted interventions to address these challenges effectively.